Case report: Formation and recurrence of inflammatory pseudotumor after metal-on-metal hip arthroplasty - Min, Meipeng; Xing, Chenyang; Xu, Peili; Wei, Xincheng; Fan, Lei (Frontiers in Medicine, 2024)
The metal-on-metal (MoM) artificial hip joint is a prosthesis used in early hip arthroplasty, particularly for hip surface arthroplasty and total hip arthroplasty. However, abrasion and corrosion of MoM bearings result in the production of metal ions such as cobalt and chromium, thereby inducing several complications such as inflammatory pseudotumor, aseptic inflammation, and allergy to metal ions (delayed type IV hypersensitivity). We here report a case of a patient hospitalized for the recurrence of a mass in the right inguinal area. In 2010, a patient underwent a right MoM total hip arthroplasty for right femoral head necrosis and exhibited a good postoperative recovery. In 2019, the patient experienced pain in the right hip with activity limitation without any evident triggers, and a palpable mass was observed in the right inguinal area. A large periprosthetic mass was resected from the patient under general anesthesia, and the patient recovered well after the operation. Based on post-surgery imaging and pathological examinations, the mass was diagnosed as a periprosthetic inflammatory pseudotumor. In 2021, the inflammatory pseudotumor recurred at the same place. He then underwent right total hip revision surgery under epidural anesthesia and recovered well after surgery. No recurrence was noted at moderate follow-up. The incidence of inflammatory pseudotumors is high in MoM hip arthroplasty. Early revision is necessary for patients who meet the indications for revision, while regular postoperative follow-up is crucial.